The Rule of Reason Approach in Discriminatory Practices: Airlines and Telecommunications Industry Sector - Sharda Abrianti; Anna Maria Tri Anggraini; Ahmad Sabirin; Joice Chintya Mardohar; Séréna Ortigosa Fernandez (Jurnal Dinamika Hukum, 2024)
Discriminatory practices are standard in business competition and are not prohibited as long as they do not cause unfair competition. This paper will discuss three Business Competition Supervisory Commission (KPPU) decisions in 2020 related to alleged discriminatory practices committed by business actors. The subject matter in this paper is how the actions of business actors can fulfil the elements of violation and how the application of the rule of reason approach in Article 19 letter d of the Competition Law (1999) in the 2020 KPPU Decisions. This research is descriptive normative research. The data used in the book, articles, the new paper analyzed the Competition Law (1999), the Airlanes law (2009), the Electronic Information and Transactions Law (2008, amendments 2016 & 2024), and the Hajj and Umarah Law (2019), as well as interview an expert and KPPU. The interesting findings found that acts of discrimination cause obstacles in vertical business relations in different but interrelated relevant markets and often occur in the essential facilities sector. By using the rule of reason approach, KPPU found that discriminatory practices will be more effective if the business actor is in a dominant position or even occupies a monopoly position. Then, the three decisions in this discussion are equally suspected of violating Article 19 letter d on discriminatory practices. Then, related to the relevant market, the three cases have different markets, and also all three have vertical relationships with other business actors.